Graphic health warnings and plain packaging in the Philippines: results of online and household surveys - Amul, Gianna Gayle H.; Mallari, Eunice U.; Arda, John Rafael Y.; Santiago, Alen Josef A. (Frontiers in Public Health, 2023)
In line with Article 11 of the WHO Framework Convention on Tobacco Control, the Philippines has implemented graphic health warnings on cigarette packs. To date, there has been no published literature evaluating the perceived effectiveness of GHWs in the Philippines. This study aims to contribute to the evidence on the perceived effects of graphic health warnings (GHWs) in cigarette packaging and the potential impact of plain packaging in the Philippines. The study involved an online convenience survey and a nationwide household survey. Mock-up sets of cigarette packs based on the Philippines’ law on GHWs, and Thailand’s and Singapore’s plain packaging were shown to respondents to rate their attractiveness, quality, taste, cost, social appeal, appeal to youth, noticeability, appeal to non-smokers, attempt to quit, ease of quitting, discouraging smoking, and perceived harm to health on a 5-point Lickert scale. The online and household surveys recruited 2,701 respondents in total. Online and household survey respondents considered plain packaging with larger graphic health warnings and visible quitlines from Thailand and Singapore to be more effective in discouraging them from smoking. Both sets of survey respondents also found mock-ups from Thailand and Singapore more motivating for them to attempt quitting than cigarette pack mock-ups from the Philippines. The study concludes that current graphic health warnings in the Philippines are ineffective in instilling health consciousness among Filipinos. Policymakers should consider larger graphic health warnings and plain packaging of cigarettes to motivate smokers to quit and discourage Filipinos from smoking.